2020
DOI: 10.1002/rra.3597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of planktonic and reed biofilm bacteria in different riverine water bodies of river Danube

Abstract: As the submerged shoot parts of common reed (Phragmites australis) can provide large surfaces for biofilm‐forming bacteria, extensive reed stands can effectively contribute to the self‐purification in the littoral zones of freshwaters. However, bacterial biofilm developed on reed surfaces have been studied only in still waters. In the present study, comparative examinations were performed on the planktonic and reed biofilm bacterial communities from two different riverine water bodies. Water and reed biofilm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Many taxa identified in this study have also been found in other rivers, and their role in the ecosystems and potential effects on human health are also known in some cases. Limnohabitans, Polynucleobacter, hgcI_clade and Sediminibacterium were recorded in rivers worldwide [16,18,[60][61][62][63][64][65]. The genus Limnohabitans includes morphologically diverse, metabolically versatile, fast-growing bacteria which play an important role in channelling carbon from primary producers to higher trophic levels [66].…”
Section: Plos Onementioning
confidence: 99%
“…Many taxa identified in this study have also been found in other rivers, and their role in the ecosystems and potential effects on human health are also known in some cases. Limnohabitans, Polynucleobacter, hgcI_clade and Sediminibacterium were recorded in rivers worldwide [16,18,[60][61][62][63][64][65]. The genus Limnohabitans includes morphologically diverse, metabolically versatile, fast-growing bacteria which play an important role in channelling carbon from primary producers to higher trophic levels [66].…”
Section: Plos Onementioning
confidence: 99%